2015
DOI: 10.5604/20834543.1142369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tobacco smoking on the choice of mode of nutrition and dietary behaviours – Preliminary study

Abstract: Wprowadzenie. Palenie tytoniu należy do najpoważniejszych współczesnych zagrożeń zdrowia człowieka, określanych również jako zagrożenia cywilizacyjne. Wiele publikacji poświęcono rozwojowi chorób wywołanych paleniem tytoniu. Natomiast stosunkowo niewiele prac dotyczy wpływu palenia tytoniu na wybór sposobu żywienia i zachowania żywieniowe. Cel. Głównym celem badań było poznanie sposobu żywienia i zachowań żywieniowych osób palących, w odniesieniu do osób niepalących. Celem dodatkowym było rozpoznanie, jak bard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 6 publications
2
5
0
Order By: Relevance
“…Authors also observed a significant but less dramatic reduction of fruit consumption in women smokers compared with nonsmoking women. The similar trends found Śmiechowska et al [9] for Polish smokers employed in an educational institution who eat fruits less than once a week and only 22% of them include vegetables to their daily diet.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…Authors also observed a significant but less dramatic reduction of fruit consumption in women smokers compared with nonsmoking women. The similar trends found Śmiechowska et al [9] for Polish smokers employed in an educational institution who eat fruits less than once a week and only 22% of them include vegetables to their daily diet.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, it has been shown that the composition of the diet of smokers was different from the diets of never-smokers, while ex-smokers had intermediate values [14][15][16]. Such few observations concern also smokers in Poland [9,17]. The authors agree that Polish smokers' diet is irregular and low in basic nutrients (protein and fiber) as compared to the non-smoking population.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations